EXAMINATION OF DIGITAL LITERACY SKILLS OF UNDERGRADUATE STUDENTS ACCORDING TO VARIOUS VARIABLES - SİBEL YOLERİ; Zeynep Nur Anadolu (Novìtnâ Osvìta)
The purpose of this research was aimed to determine the digital literacy skills of undergraduate students studying in different departments of the university according to the variables of gender, type of faculty, and daily internet use. In order to achieve this goal, 388 undergraduate students studying at the Faculty of Education, Faculty of Health Sciences, and Faculty of Economics and Administrative Sciences at İzmir Democracy University were determined as participants. The “Personal Information Form” prepared by the researchers and the “Digital Literacy Scale (DLS)” developed by Bayrakcı & Narmanlıoğlu (2021) and consisting of six sub-dimensions were used as data collection tools. According to the findings of the research, it was determined that the digital literacy levels of the students were moderate. When examined according to the gender variable, a significant difference was found between female and male students in the sub-dimensions of digital literacy levels. When examined according to the faculty variable, it was determined that there was a significant difference between the sub-dimensions of digital literacy levels, Daily Use, Professional Production, and Privacy and Security. As a result of the research, according to the daily internet usage variable, a significant difference was found between the General Knowledge and Functional Skills sub-dimensions of the digital literacy levels of the students according to the daily internet usage time. It is expected that the results obtained will contribute to the literature and draw attention to the development of digital literacy skills of university students.